PENGARUH KONSENTRASI DAN ION VALENSI LARUTAN TERHADAP RAPAT ARUS DIFUSI ION PADA MEMBRAN KITOSAN - Hariyani, Umi; Rupiasih, Ni Nyoman; Antha Kasmawan, I Gde (BULETIN FISIKA; Vol 14 No 2 (2013): BULETIN FISIKA, 2013)
An investigation of the effect of concentration and ion valence of solution on the current density on biopolymer chitosan membrane has been done. The study aimed to determine the current-voltage characteristics of chitosan membrane especially for ion diffusion. Membrane used was chitosan membrane with matrix of 2%, and the electrolyte solution was NaCl (ionic valence+1) and CaCl 2 (ionic valence+2), with various concentration of 0.1 mM, 1mM, 10mM, 100mM and 1000mM. Transport process is done by using a model cell membrane consisting of 2 rooms. The voltage difference of membrane is measured using “a calomel electrode of Activon AEP Single Jnct 12x120 mm”. From the observations obtained, the higher concentration difference in the both rooms and the greater value of ion valence, the current density of ionic diffusion increased, especially at the highest concentration difference e.g. 1000 mM: 0.1 mM, the diffusion force generated was large enough.